LA QUETOTAXIA DE LA LARVA DE ANOPHELES OCCIDENTALIS DYAR Y KNAB - CORREA, M L (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1944)
The author analyzes 44 characters in the chaetotaxy of 54 larvae of A occidentalis (4th instar) from the Valley of Mexico (2240 m altitude) and finds a considerable variability According to the number of ante-palmate hairs, the Mexican form of the mac
AN ESC NAC CIENC BIOL
Keywords: QUETOTAXIA, LARVA, ANOPHELES, OCCIDENTALIS; CIENCIAS MEDICAS; ENTOMOLOGIA